A handheld luminometer with sub-attomole limit of detection for distributed applications in global health. - Paul Lebel; Susanna Elledge; Diane M Wiener; Ilakkiyan Jeyakumar; Maíra Phelps; Axel Jacobsen; Emily Huynh; Chris Charlton; Robert Puccinelli; Prasenjit Mondal; Senjuti Saha; Cristina M Tato; et al. (PLOS Global Public Health, 2024)
Luminescence is ubiquitous in biology research and medicine. Conceptually simple, the detection of luminescence nonetheless faces technical challenges because relevant signals can exhibit exceptionally low radiant power densities. Although low light detection is well-established in centralized laboratory settings, the cost, size, and environmental requirements of high-performance benchtop luminometers are not compatible with geographically-distributed global health studies or resource-constrained settings. Here we present the design and application of a ~$700 US handheld, battery-powered luminometer with performance on par with high-end benchtop instruments. By pairing robust and inexpensive Silicon Photomultiplier (SiPM) sensors with a low-profile shutter system, our design compensates for sensor non-idealities and thermal drift, achieving a limit of detection of 1.6E-19 moles of firefly luciferase. Using these devices, we performed two pilot cross-sectional serology studies to assess sars-cov-2 antibody levels: a cohort in the United States, as well as a field study in Bangladesh. Results from both studies were consistent with previous work and demonstrate the device's suitability for distributed applications in global health.